2016
DOI: 10.4082/kjfm.2016.37.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Blood Mercury Concentration and Bone Mineral Density in Korean Men in the 2008–2010 Korean National Health and Nutrition Examination Survey

Abstract: BackgroundThe results of previous studies on the association between blood mercury (Hg) and bone mineral density (BMD) are inconsistent. We therefore used a large-scale nationwide representative sample of Korean men to investigate the relationship between these two parameters.MethodsA nationwide cross-sectional study was conducted using data from the 2008 to 2010 Korean National Health and Nutrition Examination Survey to evaluate the relationship between blood Hg and BMD and the prevalence of osteopenia or ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Comparing to literature data, Zioła-Frankowska et al 27 also did not show statistical significance between the patient's age and mercury concentration in femoral bone from those undergoing hip surgery. 27 In turn, Kim et al 13 noticed higher mercury levels in young men compared to older ones. 13 The same work also analysed the effect of blood mercury on bone density and osteoporosis in Korean men.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Comparing to literature data, Zioła-Frankowska et al 27 also did not show statistical significance between the patient's age and mercury concentration in femoral bone from those undergoing hip surgery. 27 In turn, Kim et al 13 noticed higher mercury levels in young men compared to older ones. 13 The same work also analysed the effect of blood mercury on bone density and osteoporosis in Korean men.…”
Section: Discussionmentioning
confidence: 97%
“…27 In turn, Kim et al 13 noticed higher mercury levels in young men compared to older ones. 13 The same work also analysed the effect of blood mercury on bone density and osteoporosis in Korean men. The authors suggested that people with higher levels of mercury in the blood have a reduced bone density and more frequent osteoporosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Phenylmercury enters in the renal tubes through the contaminated diapers, with the excretion of gamma glutamyl transpeptidase in renal cells leading to increase urinary volume and toxicity. Osteoporosis and osteopenia diseases in Korean men due to mercury were studied by Kim et al [48]. The analysis was performed on Korean men's blood samples, and high mercury range in younger people was found.…”
Section: Renal and Bone-related Effects Due To Mercury Poisoningmentioning
confidence: 99%